1997
DOI: 10.1002/(sici)1097-0142(19970201)79:3<448::aid-cncr4>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline sphingomyelinase activity is decreased in human colorectal carcinoma

Abstract: perimental colon carcinoma in mice, indicating that the abnormal metabolism of sphingomyelin is linked to colon carcinoma development. However, the changes 1 Department of Medicine, Lund University Hospital, Lund, Sweden.in sphingomyelinase (SMase) activity in colon carcinoma have not been directly studied. The authors identified, specifically in the intestine, a distinctive alkaline 2 Research Park Ideon, Swedish Dairies AssociSMase that differs from the known acidic and neutral SMases. The functions and atio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 2 publications
(2 reference statements)
2
25
0
Order By: Relevance
“…In previous studies we found reduced alkaline SMase activity in sporadic colorectal adenomas, in colorectal carcinomas, and in patients with familial adenomatous polyposis both in adenomas and flat mucosa (10,11).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In previous studies we found reduced alkaline SMase activity in sporadic colorectal adenomas, in colorectal carcinomas, and in patients with familial adenomatous polyposis both in adenomas and flat mucosa (10,11).…”
Section: Introductionmentioning
confidence: 74%
“…DNA ploidy measurement is therefore used as another objective marker for malignant transformation at some centers. Alkaline SMase activity has previously been found to be reduced by 50% in colorectal adenomas, by 75% in colorectal cancer, and by 90% in the adenomas and flat mucosa of familial adenomatous polyposis patients (10,11). Furthermore, ursodeoxycholate, which has been shown to be preventive in experimental colorectal carcinogenesis (25), has been found to increase alkaline SMase activity in colorectal mucosa (26).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported on the presence of ceramide and ceramidase in cancer tissues. In human colorectal carcinoma, according to Hertervig et al (1997), cellular levels of ceramide are low due to decreased sphingomyelinase activity, and ceramidase activity is not altered. In the present study, levels of AC mRNA were decreased in thyroid tumor tissues, especially in anaplastic carcinomas, suggesting decreased AC activity in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence indicates that activation of alkaline sphingomyelinase in the human colon functions as an antiproliferative pathway through its generation of ceramides [31]. Reduction in alkaline sphingomyelinase activity has been reported in human colon cancers and mutations in the enzyme exist in transformed human colon cancer cell lines [32, 33].…”
Section: Mechanisms Of Anticancer Activity Of Phytosterolsmentioning
confidence: 99%